Iodine Leaf Gum Gel (Jatropha Multifida Linn) to Accelerate the Healing Process of Grade II Burn Wounds in Mice (Mus Musculus Linn) - Wardani, Annisa Wahyu; Kurniawan, Sahuri Teguh; Saelan, Saelan; Sulisetyawati, S. Dwi; Priambodo, Galih (GLOBAL HEALTH SCIENCE GROUP, 2024)
Burns are a serious emergency that necessitates immediate intervention to save lives. Iodine leaf sap (Jatropha multifida Linn) contains saponins, tannins, alkaloids and flavonoids which are successful in speeding up the recuperating of consume wounds. Research Objective: Determine the effect of iodine leaf plastic gel on the improvement of level II consumption in male mice (Mus musculus Linn). Objective: The examination plans to decide the impact of iodine leaf plastic gel on mending grade II consumes in male mice (Mus musculus Linn). Method: The exploration utilized the genuine trial research facility strategy through a post test just control configuration bunch plan in the lab at Kusuma Husada College, Surakarta. Involving 24 mice as guinea pigs, they were partitioned into 3 gatherings, to be specific positive control, negative control and iodine leaf sap gel. 1.5 centimeters of hot metal were attached to the mice's backs for five to ten seconds to produce burn wounds. The area of the burn wound, the percentage of healing, and the time it took for the burn wound to heal were the parameters that were observed. Results: Information investigation utilized the One-Way ANOVA test. The consequences of the review showed that iodine leaf plastic gel made some mending memories of 8 days and a level of 30.75% better recuperating of consume wounds contrasted with the other benchmark groups. The factual experimental outcomes expressed that it was huge (<0.05) in the level of consume wound mending. Conclusions: The study's conclusion was that compared to the other control groups, iodine leaf latex gel at a concentration of 6% improved burn healing.